The puppet as a tool for working in Art Therapy - Eva Cristina Mesas Escobar (Arteterapia, 2016)
This article aims to investigate the possibilities of building puppets in art therapy workshop, for this it realizes a tour of the primitive use of the puppet as a magical twin and potential towards the study of authors who have used the puppets as a therapeutic tool from the first half of the twentieth century. It’s raised an own theoretical organization, which includes the consideration of the significance of the body in the construction and management of the puppet and the puppet transitional perspective, halfway of external reality and psychic reality as an object that makes fantasy and reality arises built.